The strategic implication of electronic commerce for small and medium sized enterprises (SME) - Quader, Mohammed Shahedul; Ahmed, Rubina I. (BRAC University, 2010)
The objective of this Paper is to examine the strategic implication of Electronic Commerce for small and medium sized enterprises. This paper explores how electronic commerce has the potential to transform the concept of market by changing firms’ business models, business relationships and market structure. By changing firms’ competitive advantages and nature of competition, electronic commerce may have strategic implications for small and medium sized enterprises. From the research undertaken, the paper draws conclusions of how electronic commerce fits into the broader context of their business and its strategy.